Electromagnetic shielding material for power equipment and preparation method and application thereof
Patent Information
- Application Number
- CN202511857635.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-10
AI Technical Summary
[0005]本发明的目的在于提供一种电力设备用电磁屏蔽材料及其制备方法与应用,解决无法同时满足低频磁场与高频电场的屏蔽需求、频谱适应性不足的问题
本发明提供一种电力设备用电磁屏蔽材料及其制备方法与应用,通过在卷对卷电沉积设备中依次构建多层复合箔a与多层复合箔b,并将二者分别破碎成多层复合箔粉末a与多层复合箔粉末b,使材料在初始阶段即获得能够在后续烧结中实现快速扩散的多界面结构,再通过将多层复合箔粉末a、多层复合箔粉末b与粘连剂混合后在梯度共混流延头内按比例输出形成沿厚度方向连续变化的初步生坯带,使材料在烧结前即平滑梯度,随后在初步生坯带表面印刷银基浆料并干燥形成银基生坯带,通过多次烧结处理使Fe、Ni、Cu元素在固态下充分互扩散并稳定形成梯度烧结材料,最终通过表面平整化处理与镍磷保护层形成使材料兼具耐腐蚀性与高频反射能力,从而使本发明制得的电磁屏蔽材料能够同时满足低频磁场对高磁导率的需求与高频电场对高导电性的需求,并通过梯度结构降低界面阻抗突变,使屏蔽效能在宽频范围内保持稳定,提高了电力设备在宽频电磁干扰环境下的运行可靠性,解决了单一材料无法兼顾低频磁场与高频电场屏蔽的问题。
Smart Images

Figure CN121645817B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic shielding, and more particularly to an electromagnetic shielding material for power equipment, its preparation method, and its application. Background Technology
[0002] Industrial high-power frequency converters, as core equipment for motor drives, are used in various types of equipment. For example, when used in mining machinery, they are generally used for energy saving, consumption reduction, and improving transmission capacity. The high-speed switching of power devices such as insulated-gate bipolar transistors (IGBTs) in the internal power units of industrial high-power frequency converters generates severe electromagnetic interference (EMI). This interference has an extremely wide spectrum, with its low-frequency components extending to the fundamental frequency of the switching frequency (usually a few kHz), while its high-frequency components are determined by the steep edges of the switching pulses, containing abundant high-order harmonics with frequencies reaching tens or even hundreds of MHz. This wide-spectrum electromagnetic pollution, ranging from low to ultra-high frequencies, not only threatens the stable operation of the frequency converter's own control circuit but may also affect the power grid quality and surrounding sensitive electronic equipment through conduction and radiation. Therefore, it is essential to effectively suppress it.
[0003] Currently, adding metal shielding covers to power units is a common method for suppressing radiated interference. These covers are typically made of conductive materials such as galvanized steel, aluminum, or copper, and may use conductive gaskets at the joints to reduce leakage. However, existing shielding solutions have limitations. For example, they cannot simultaneously meet the shielding requirements for low-frequency magnetic fields and high-frequency electric fields, and their spectral adaptability is insufficient. Specifically, for the wide-spectrum electromagnetic interference (covering everything from low-frequency magnetic fields to high-frequency electric fields) generated by inverter power units, traditional single-material shielding covers often cannot effectively suppress the entire frequency band, especially... Under the interference of low-frequency strong magnetic fields generated by high-current busbars, shielding with a single material cannot effectively suppress the interference. The suppression effect of a single metal material on electromagnetic interference varies significantly across different frequency bands. Highly conductive materials have good shielding effect on high-frequency electric fields, but poor shielding effect on low-frequency magnetic fields. Shielding of low-frequency magnetic fields mainly relies on the high permeability of the material. However, existing highly conductive materials cannot provide sufficient permeability to absorb low-frequency magnetic fields. Although using materials that rely solely on high permeability to shield low-frequency magnetic fields is effective, it leads to increased equipment weight, higher costs, and poor suppression effect on high-frequency radiation.
[0004] Therefore, an electromagnetic shielding material for power equipment, its preparation method, and its application are proposed to solve the problems of insufficient shielding requirements for both low-frequency magnetic fields and high-frequency electric fields, and inadequate spectral adaptability. Summary of the Invention
[0005] The purpose of this invention is to provide an electromagnetic shielding material for power equipment, its preparation method and application, to solve the problems of not being able to simultaneously meet the shielding requirements of low-frequency magnetic fields and high-frequency electric fields, and insufficient spectrum adaptability.
[0006] To achieve this objective, the present invention adopts the following technical solution: A method for preparing an electromagnetic shielding material for power equipment, the method comprising the following steps: Step S1: Prepare multilayer composite foils a and b, which are composed of alternating Fe-Ni layers and Cu layers, and crush them into multilayer composite foil powder a and multilayer composite foil powder b, respectively. Step S2: Mix the adhesive with multilayer composite foil powder a and multilayer composite foil powder b respectively to obtain slurry a and slurry b. Then, perform gradient casting on slurry a and slurry b to obtain a preliminary green strip. Then, print the silver-based slurry on the preliminary green strip to obtain a silver-based green strip. Step S3: After segmented degreasing of the silver-based green strip, it is subjected to low-temperature activation sintering, followed by high-temperature densification sintering to obtain a gradient sintered material. Step S4: After surface smoothing treatment of the gradient sintering material, a nickel-phosphorus protective layer is formed on its surface by chemical plating to obtain the electromagnetic shielding material.
[0007] Step S1 specifically includes the following steps: Step S11: First, in the roll-to-roll electrodeposition equipment, the electrodeposition cathode carrier a is sequentially passed through the magnetic layer electrodeposition tank, the cleaning tank, and the conductive layer electrodeposition tank. After multiple cycles, Fe-Ni and Cu layers are alternately deposited on the electrodeposition cathode carrier a to obtain a multilayer composite foil a with Fe-Ni layer as the outermost layer. Subsequently, the electrodeposition cathode carrier b is sequentially passed through the conductive layer electrodeposition tank, the cleaning tank, and the magnetic layer electrodeposition tank. After multiple cycles, Cu and Fe-Ni layers are alternately deposited on the electrodeposition cathode carrier b to obtain a multilayer composite foil b with Cu layer as the outermost layer. Step S12: By shearing pre-shredding and inert atmosphere airflow pulverization, multilayer composite foil a and multilayer composite foil b are respectively made into sheet powder, resulting in multilayer composite foil powder a and multilayer composite foil powder b.
[0008] In step S11, the magnetic layer electrodeposition tank is filled with electrolyte a, which contains 80-120 g / L ferrous sulfate and 5-15 g / L nickel sulfate, and the pH value of electrolyte a is 2.5-3.5, the temperature is 45-55℃, and the current density of the magnetic layer electrodeposition tank is 8-12 A / dm³. 2The conductive layer electrodeposition tank is filled with electrolyte b, which contains 60-100 g / L copper sulfate and 80-120 g / L sulfuric acid, and the temperature of electrolyte b is 25-35°C. The current density of the conductive layer electrodeposition tank is 4-6 A / dm³. 2 The total number of layers of the multilayer composite foil a and the multilayer composite foil b are both 40-80 layers, the thickness of a single layer is both 80-200nm, and the total thickness is both 6.4-16μm. The atomic ratio of (Fe-Ni) to Cu in the multilayer composite foil a is (55-65):(35-45), and the atomic ratio of (Fe-Ni) to Cu in the multilayer composite foil b is (30-40):(60-70). In step S12, the average particle size D50 of the multilayer composite foil powder a and the multilayer composite foil powder b are both 15-35μm, the particle size is both 5-45μm, the powder thickness is both 2-4μm, and the aspect ratio is both >10.
[0009] Step S2 specifically includes the following steps: Step S21: Mix multilayer composite foil powder a with adhesive in a certain proportion and then ball mill to obtain slurry a; mix multilayer composite foil powder b with adhesive in a certain proportion and then ball mill to obtain slurry b; Step S22: After feeding slurry a and slurry b into the gradient blending casting head, adjust the feeding ratio of slurry a and slurry b, and output the wet film from the gradient blending casting head along the magnetic side to the conductive side to form a wet film. Then, perform initial drying on the wet film to obtain a preliminary green belt. Step S23: Silver-based paste is printed onto a predetermined area on the initial green belt using screen printing, and then dried again to obtain a silver-based green belt.
[0010] In step S21, the adhesive comprises 5-8 wt% polyvinyl butyral, 3-4 wt% dibutyl phthalate, 1-2 wt% dispersant, and the balance being an ethanol-toluene mixed solvent. The multilayer composite foil powder a and multilayer composite foil powder b have the same mass ratio to the adhesive, which is (70-75):(25-30). The apparent viscosity of slurry a and slurry b is 2000-4000 cP. In step S22, the casting speed of the gradient blending casting head is 0.6-0.8 m / min, the thickness of the wet film is 1.0-1.3 mm, the thickness of the initial green belt is 0.7-0.9 mm, and in the wet film, along the direction from the magnetic side to the conductive side, the proportion of slurry a decreases sequentially, while the proportion of slurry b increases sequentially. The initial drying temperature is 40-60℃ and the time is 20-40 min. In step S23, the silver-based paste contains 60-75 wt% silver powder, 10-20 wt% borosilicate glass powder, and 10-20 wt% organic carrier. The silver powder has a particle size of 2-5 μm, the borosilicate glass powder has a particle size of 1-3 μm and a softening point of 750-850℃, the printing thickness of the silver-based paste is 10-30 μm, and the re-drying temperature is 40-60℃ and the time is 20-40 min.
[0011] Step S3 specifically includes the following steps: Step S31: Place the silver-based green strip in a sintering furnace under a nitrogen protective atmosphere and perform low-temperature stage and medium-temperature stage in sequence to obtain green body a; Step S32: Raise the temperature of the environment where embryo a is located to the first temperature to obtain embryo b; Step S33: Raise the temperature of the environment where the preform b is located to a second temperature and apply pressure to it to obtain a gradient sintering material.
[0012] In step S31, the heating rate of the low-temperature stage is 0.5-1℃ / min, the temperature is 200-250℃, and the duration is 1-2h; the heating rate of the medium-temperature stage is 0.5-1℃ / min, the temperature is 350-450℃, and the duration is 2-3h. In step S32, the first temperature is 780-820℃, the heating rate is 3-5℃ / min, and the duration is 1-2h; In step S33, the second temperature is 860-900℃, the heating rate is 2-4℃ / min, the duration is 0.5-1h, and the pressure is 0.5-2MPa.
[0013] Step S4 specifically includes the following steps: Step S41: Perform surface planarization treatment on the gradient sintering material to make its surface roughness Ra 0.8-1.6μm; Step S42: A nickel-phosphorus protective layer is formed by electroless plating on the surface of the gradient sintering material to obtain an electromagnetic shielding material; wherein the thickness of the nickel-phosphorus protective layer is 1-2 μm, the phosphorus content is 6-10 wt%, and the plating temperature is 80-90℃.
[0014] An electromagnetic shielding material for power equipment, wherein the electromagnetic shielding material for power equipment is obtained according to the preparation method described above.
[0015] Application of an electromagnetic shielding material for power equipment prepared according to the above-described method in the field of electromagnetic interference suppression.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention provides an electromagnetic shielding material for power equipment, its preparation method, and its application. Multilayer composite foils a and b are sequentially constructed in a roll-to-roll electrodeposition apparatus, and then broken into multilayer composite foil powders a and b, respectively. This allows the material to acquire a multi-interface structure capable of rapid diffusion during subsequent sintering in the initial stage. The multilayer composite foil powders a and b are then mixed with a binder and output proportionally in a gradient blending casting head to form a preliminary green strip with a continuously varying thickness direction. This smooths the gradient of the material before sintering. Subsequently, a silver-based paste is printed on the surface of the preliminary green strip and dried to form… The silver-based green strip undergoes multiple sintering processes to allow Fe, Ni, and Cu elements to fully interdiffuse in the solid state and stabilize into a gradient sintered material. Finally, surface smoothing and the formation of a nickel-phosphorus protective layer endow the material with both corrosion resistance and high-frequency reflection capability. This allows the electromagnetic shielding material prepared by this invention to simultaneously meet the requirements of high permeability for low-frequency magnetic fields and high conductivity for high-frequency electric fields. Furthermore, the gradient structure reduces abrupt changes in interface impedance, ensuring stable shielding effectiveness over a wide frequency range. This improves the operational reliability of power equipment in broadband electromagnetic interference environments and solves the problem that a single material cannot simultaneously shield both low-frequency magnetic fields and high-frequency electric fields. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] The structures, proportions, sizes, etc., shown in the accompanying drawings of this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed in the specification, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.
[0019] Figure 1 This is a flowchart of the preparation method in this invention. Detailed Implementation
[0020] To make the objectives, features, and advantages of this invention more apparent and understandable, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0021] In the description of this invention, it should be understood that the terms "upper," "lower," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. It should be noted that when a component is considered to be "connected" to another component, it can be directly connected to the other component or there may be a component positioned centrally in the connection.
[0022] Example 1: Please see Figure 1 This embodiment describes a method for preparing an electromagnetic shielding material for power equipment, which includes the following steps: Step S1: Prepare multilayer composite foils a and b, which are composed of alternating Fe-Ni layers and Cu layers, and crush them into multilayer composite foil powder a and multilayer composite foil powder b, respectively. Step S2: Mix the adhesive with multilayer composite foil powder a and multilayer composite foil powder b respectively to obtain slurry a and slurry b. Then, perform gradient casting on slurry a and slurry b to obtain a preliminary green strip. Then, print the silver-based slurry on the preliminary green strip to obtain a silver-based green strip. Step S3: After segmented degreasing of the silver-based green strip, it is subjected to low-temperature activation sintering, followed by high-temperature densification sintering to obtain a gradient sintered material. Step S4: After surface smoothing treatment of the gradient sintering material, a nickel-phosphorus protective layer is formed on its surface by chemical plating to obtain the electromagnetic shielding material.
[0023] Specifically, in step S1, a multilayer composite foil a and a multilayer composite foil b consisting of alternating Fe-Ni layers and Cu layers are prepared, and the two are crushed into multilayer composite foil powder a and multilayer composite foil powder b, respectively. Step S1 specifically includes the following steps: Step S11: First, in the roll-to-roll electrodeposition equipment, the electrodeposition cathode carrier a is sequentially passed through the magnetic layer electrodeposition tank, the cleaning tank, and the conductive layer electrodeposition tank. After multiple cycles, Fe-Ni and Cu layers are alternately deposited on the electrodeposition cathode carrier a to obtain a multilayer composite foil a with Fe-Ni layer as the outermost layer. Subsequently, the electrodeposition cathode carrier b is sequentially passed through the conductive layer electrodeposition tank, the cleaning tank, and the magnetic layer electrodeposition tank. After multiple cycles, Cu and Fe-Ni layers are alternately deposited on the electrodeposition cathode carrier b to obtain a multilayer composite foil b with Cu layer as the outermost layer. In step S11, the magnetic layer electrodeposition tank is filled with electrolyte a, which contains 80-120 g / L ferrous sulfate and 5-15 g / L nickel sulfate. The pH of electrolyte a is 2.5-3.5, the temperature is 45-55℃, and the current density of the magnetic layer electrodeposition tank is 8-12 A / dm³. 2 The conductive layer electrodeposition tank is filled with electrolyte b, which contains 60-100 g / L copper sulfate and 80-120 g / L sulfuric acid. The temperature of electrolyte b is 25-35℃, and the current density of the conductive layer electrodeposition tank is 4-6 A / dm³. 2 The total number of layers of multilayer composite foil a and multilayer composite foil b are both 40-80 layers, the thickness of a single layer is both 80-200nm, and the total thickness is both 6.4-16μm. The atomic ratio of (Fe-Ni) to Cu in multilayer composite foil a is (55-65):(35-45), and the atomic ratio of (Fe-Ni) to Cu in multilayer composite foil b is (30-40):(60-70). Step S12: By shearing pre-shredding and inert atmosphere airflow pulverization, multilayer composite foil a and multilayer composite foil b are respectively made into sheet powder, resulting in multilayer composite foil powder a and multilayer composite foil powder b.
[0024] In step S12, the average particle size D50 of the multilayer composite foil powder a and the multilayer composite foil powder b are both 15-35 μm, the particle size is both 5-45 μm, the powder thickness is both 2-4 μm, and the aspect ratio is both >10.
[0025] It should be noted that in step S11, the electrodeposition cathode carrier a passes sequentially through a magnetic layer electrodeposition tank, a cleaning tank, and a conductive layer electrodeposition tank in the roll-to-roll electrodeposition equipment. In the magnetic layer electrodeposition tank, the Fe provided by the ferrous sulfate and nickel sulfate in the electrolyte a... 2+ and Ni 2+ Electrochemical reduction occurs on the surface of the electrodeposition cathode carrier a at a set pH value, current density, and temperature, forming a Fe-Ni solid solution magnetic layer with controllable composition; in the conductive layer electrodeposition tank, Cu in the electrolyte b... 2+Under set current density and temperature, the material is reduced to a Cu metal conductive layer. The electrodeposition cathode carrier a circulates repeatedly between two electrodeposition tanks, with residual electrolyte removed in an intermediate cleaning tank. This process achieves alternating deposition of Fe-Ni and Cu layers, forming a multilayer composite foil a. Its outermost layer is a Fe-Ni layer, and the overall atomic ratio of Fe-Ni to Cu is (55-65):(35-45). Similarly, the electrodeposition cathode carrier b passes through the conductive layer electrodeposition tank, cleaning tank, and magnetic layer electrodeposition tank in reverse order, alternatingly depositing Cu and Fe-Ni layers on its surface. The multilayer composite foil b, with Cu as the outermost layer, has the same total number of layers, single-layer thickness, and total thickness as the multilayer composite foil a, but the overall atomic ratio of (Fe-Ni) to Cu is (30-40):(60-70). In the above process, both multilayer composite foil a and multilayer composite foil b form a regular Fe-Ni and Cu alternating nano-multilayer structure in the thickness direction, with clear interfaces, uniform layer thickness, and continuous metal strip shape. In addition, Fe-Ni solid solution is formed inside the Fe-Ni layer, the Cu layer is a highly conductive metal layer, and the Fe-Ni and Cu interface serves as a high-energy interface for subsequent diffusion.
[0026] In step S12, the multilayer composite foils a and b, which are in the form of continuous metal strips, are first sheared and pre-crushed, cutting the continuous strip material into strips with smaller widths. Then, under inert atmosphere airflow pulverization conditions, the strip material is further crushed into sheet-like particles by high-speed airflow impact and shearing action, resulting in multilayer composite foil powder a and multilayer composite foil powder b. In this process, although the multilayer composite foil powders a and b are reduced to individual sheet-like particles in terms of geometric size, each sheet-like particle still retains the alternating Fe-Ni and Cu layer structure along the thickness direction. The internal micro-layer structure and overall composition ratio are not destroyed. After shearing and pulverization, the multilayer composite foil powders a and b are transformed from strip material into powder material suitable for mixing, slurry preparation, and casting, providing good processability for subsequent processes.
[0027] It is known that the outermost layer of the multilayer composite foil a is an Fe-Ni layer, and the atomic ratio of (Fe-Ni) to Cu inside is controlled at (55-65):(35-45), making the multilayer composite foil a exhibit a high magnetic content and ferromagnetic phase content, which can serve as a precursor for the magnetic region in electromagnetic shielding materials. In contrast, the outermost layer of the multilayer composite foil b is a Cu layer, and the atomic ratio of (Fe-Ni) to Cu inside is (30-40):(60-70), exhibiting a high conductive content, which can also serve as a precursor for the conductive region in electromagnetic shielding materials. Under the action of step S12, the multilayer composite foils a and b are transformed into multilayer composite foil powders a and b, respectively, with an aspect ratio greater than 10 and in sheet form, which is beneficial for… During the subsequent casting process, the two powders are overlapped and densely packed. The particle size distribution of the two powders is concentrated in 5-45μm, and the average particle size D50 is 15-35μm. This ensures good flowability and facilitates sintering densification. In addition, the powder thickness is 2-4μm, combined with the internal 80-200nm monolayer thickness, so that each powder particle still contains a large number of Fe-Ni and Cu layered interfaces. These multilayer interfaces can serve as preferential channels for element diffusion and phase transformation during subsequent low-temperature activation sintering. This allows for the formation of Fe-Ni-Cu solid solution particles with uniform composition at lower temperatures and shorter durations, improving structural stability and electromagnetic response uniformity. This provides a local functional basis for the broadband performance of the final electromagnetic shielding material.
[0028] It is understandable that step S11 involves alternating deposition of electrodeposited cathode carriers a and b in electrolytes a and b to form multilayer composite foils a and b, achieving controllable nano-multilayer composites of the Fe-Ni and Cu system. By introducing Ni into the Fe-Ni layer, diffusion and solid-solution channels between the Fe-Ni and Cu layers can be established during subsequent sintering through Ni, a mutually soluble element. This allows for compositional adjustment through solid-state diffusion without using melting processes or raising the temperature above the Cu melting point, solving the problems of almost immiscibility between Fe and Cu in equilibrium and the tendency for severe phase separation and discontinuous electromagnetic properties when directly mixing and sintering Fe and Cu powders. By controlling the (Fe-Ni):Cu atomic ratio range in multilayer composite foils a and b, they maintain respectively high magnetic and high conductivity characteristics, providing two reference endpoints for the subsequent formation of a material structure with a continuous gradient from magnetic to conductive electromagnetic properties. Step S12 further integrates the multilayer composite... Foil a and multilayer composite foil b are transformed into multilayer composite foil powder a and multilayer composite foil powder b. This not only maintains the internal multilayer structure and overall composition, but also obtains a geometric morphology and particle size distribution suitable for slurry preparation and casting. This allows for subsequent adjustment of the mixing ratio of multilayer composite foil powder a and multilayer composite foil powder b in the thickness direction to achieve a macroscopic compositional gradient arrangement. Through the combination of the macroscopic powder ratio gradient and the diffusion advantage of the microscopic multilayer structure, densification can be achieved at a lower sintering temperature during the subsequent sintering stage. Furthermore, a compositional and structural gradient can be formed in the material thickness direction, gradually transitioning from a magnetically rich region through a transition region to a conductive region. This results in electromagnetic shielding materials with good magnetic loss absorption capacity in the low-frequency band and good conductive reflection capacity in the high-frequency band. At the same time, due to the gentle compositional gradient in the intermediate transition region, the interface impedance jump is reduced, and the broadband shielding effect is smoother. This solves the technical problem that traditional homogeneous materials cannot simultaneously achieve multi-band shielding performance when generating broadband electromagnetic interference in power equipment during high-power conversion.
[0029] It is important to emphasize that step S11, by constructing multilayer composite foils a and b on electrodeposited cathode carriers a and b respectively, divides the precursor materials into magnetic-rich and conductive ends from the outset. These differ not only in their overall atomic ratio but also in their layered structure and the type of their outermost metal. The outermost layer of multilayer composite foil a is an Fe-Ni layer, which is beneficial for matching the environment of the subsequent magnetic-rich side (regions with a higher Fe-Ni ratio). Conversely, the outermost layer of multilayer composite foil b is a Cu layer, which is beneficial for the electrical contact and reflection characteristics of the subsequent conductive side (regions with a higher Cu ratio). This difference eliminates the need for subsequent gradient implementation using multiple completely different alloy systems; instead, the gradient can be achieved within the same Fe-Ni-Cu system. The gradient is constructed internally through a combination of magnetic and conductive precursors, which simplifies the system complexity, improves material stability, and provides an adjustable intrinsic parameter space for broadband electromagnetic shielding. Step S12 converts the composite foil into powder, so that the multilayer composite foil a and multilayer composite foil b are no longer limited to simple physical stacking. Instead, through the mixing of multilayer composite foil powder a and multilayer composite foil powder b, gradient casting and other processes, an arbitrary proportional distribution is achieved in the thickness direction, ensuring that a continuous gradient is achieved rather than a discrete layered structure. This changes the performance of the electromagnetic shielding material from the interface-dominated interlayer effect to the volume-dominated gradient effect, reducing the loss and local hot spots caused by multiple reflections at the interface, and improving the stability and reliability in practical applications.
[0030] It is worth noting that in Part 5, it is explained why a roll-to-roll electrodeposition process must be used in step S11 to prepare multilayer composite foils a and b consisting of alternating Fe-Ni and Cu layers, and why shear pre-shrinking and inert atmosphere airflow pulverization must be used in step S12 to prepare multilayer composite foil powders a and b, as well as how the composition ratio of the materials and the process parameters should be coordinated to achieve the expected technical effect.
[0031] The roll-to-roll electrodeposition process in step S11 has the advantages of continuous length and precise controllability in thickness. By controlling the composition of electrolytes a and b, temperature, current density, and single pass time on the electrodeposition cathode carriers a and b, the thickness of each Fe-Ni and Cu layer can be stabilized at 80-200 nm, with a total number of layers controlled at 40-80, and a final total thickness controlled at 6.4-16 μm. Furthermore, by adjusting the ratio of Fe-Ni electrodeposition time to Cu electrodeposition time, the atomic ratio of (Fe-Ni) to Cu in multilayer composite foil a and multilayer composite foil b can be achieved. This process and the appropriate ratio ensure both the reasonable dimensionality of the layered structure and the overall... Functional zoning of components; In step S12, shear pre-shredding is used to cut the continuous multilayer composite foil a and multilayer composite foil b into small strips of appropriate size to avoid direct entry into airflow pulverization and causing entanglement and blockage; then, in inert atmosphere airflow pulverization, by adjusting process parameters such as airflow speed and impact intensity, the multilayer composite foil a and multilayer composite foil b are crushed into sheet-like multilayer composite foil powder a and multilayer composite foil powder b of appropriate size, and oxidation is suppressed under inert atmosphere. This sheet-like powder of appropriate size matches the subsequent slurry rheological requirements and sintering densification requirements, so that the powder is easy to spread and can form a high-density accumulation during the casting process, thereby laying the foundation for the formation of the initial green belt in the subsequent gradient casting. In addition, shear pre-shredding and airflow pulverization are well known to those skilled in the art, and will not be described in detail in this embodiment.
[0032] In a specific embodiment, in step S11, electrolyte a contains 100 g / L ferrous sulfate and 10 g / L nickel sulfate, and the pH value of electrolyte a is 3.0, the temperature is 50°C, and the current density of the magnetic layer electrodeposition tank is 10 A / dm². Electrolyte b contains 80 g / L copper sulfate and 100 g / L sulfuric acid, the temperature of electrolyte b is 30°C, the current density of the conductive layer electrodeposition tank is 5 A / dm², and the total number of layers of both multilayer composite foil a and multilayer composite foil b is 60 layers, the thickness of each single layer is 140 nm, and the total thickness is... The particle size is 8.4 μm. In multilayer composite foil a, the atomic ratio of (Fe-Ni) to Cu is 60:40, and in multilayer composite foil b, the atomic ratio of (Fe-Ni) to Cu is 35:65. In step S12, the average particle size D50 of multilayer composite foil powder a and multilayer composite foil powder b are both 25 μm, the particle size is 5-45 μm, the powder thickness is 3 μm, and the aspect ratio is >10. In addition, the cleaning tank is preferably set as a multi-stage countercurrent spray cleaning to avoid electrolyte residue causing corrosion, thereby ensuring a clear interlayer interface. Specifically, in step S2, the adhesive is mixed with multilayer composite foil powder a and multilayer composite foil powder b to obtain slurry a and slurry b, and then slurry a and slurry b are subjected to gradient casting to obtain a preliminary green strip. Then, silver-based slurry is printed on the preliminary green strip to obtain a silver-based green strip. Step S2 specifically includes the following steps: Step S21: Mix multilayer composite foil powder a with adhesive in a certain proportion and then ball mill to obtain slurry a; mix multilayer composite foil powder b with adhesive in a certain proportion and then ball mill to obtain slurry b; In step S21, the adhesive includes 5-8 wt% polyvinyl butyral, 3-4 wt% dibutyl phthalate, and 1-2 wt% dispersant, with the balance being an ethanol-toluene mixed solvent. The mass ratio of multilayer composite foil powder a and multilayer composite foil powder b to the adhesive is the same, which is (70-75):(25-30). The apparent viscosity of slurry a and slurry b is 2000-4000 cP. Step S22: After feeding slurry a and slurry b into the gradient blending casting head, adjust the feeding ratio of slurry a and slurry b, and output the wet film from the gradient blending casting head along the magnetic side to the conductive side to form a wet film. Then, perform initial drying on the wet film to obtain a preliminary green belt. In step S22, the casting speed of the gradient blending casting head is 0.6-0.8 m / min, the thickness of the wet film is 1.0-1.3 mm, the thickness of the initial green belt is 0.7-0.9 mm, and in the wet film, along the direction from the magnetic side to the conductive side, the proportion of slurry a decreases sequentially and the proportion of slurry b increases sequentially. The initial drying temperature is 40-60℃ and the time is 20-40 min. Step S23: Silver-based paste is screen-printed onto a predetermined area (the area where high-frequency radiation needs to be suppressed) on the initial green belt, and then dried again to obtain a silver-based green belt.
[0033] In step S23, the silver-based paste contains 60-75 wt% silver powder, 10-20 wt% borosilicate glass powder, and 10-20 wt% organic carrier. The particle size of the silver powder is 2-5 μm, the particle size of the borosilicate glass powder is 1-3 μm, the softening point is 750-850℃, the printing thickness of the silver-based paste is 10-30 μm, and the re-drying temperature is 40-60℃ for 20-40 min.
[0034] It should be noted that in step S21, multilayer composite foil powder a and multilayer composite foil powder b are mixed with an adhesive at a mass ratio of (70-75):(25-30). The adhesive consists of 5-8 wt% polyvinyl butyral, 3-4 wt% dibutyl phthalate, 1-2 wt% dispersant, and the balance being an ethanol-toluene mixed solvent. During ball milling, the ethanol-toluene mixed solvent first wets and impregnates the surfaces of multilayer composite foil powder a and multilayer composite foil powder b. Polyvinyl butyral forms polymer segments in the solvent, gradually coating the powder. On the outer surface of the particles, dibutyl phthalate enters the molecular chains of polyvinyl butyral and acts as a plasticizer, giving the subsequent drying film toughness. The dispersant is adsorbed on the powder surface, reducing the interfacial energy between powders and preventing the agglomeration of flaky particles. In this process, the Fe-Ni / Cu multilayer structure formed in step S1 remains unchanged inside each multilayer composite foil powder particle, while an organic coating layer containing polyvinyl butyral and dispersant is formed on the surface, allowing the powder to be stably suspended in the solvent in the form of single particles, exhibiting an apparent viscosity of 2000-4000 cP. Slurries a and b are suitable for input into a gradient blending casting head (a casting device with a dual-channel structure, where each channel is allocated a different slurry, and a wet film with gradually changing composition in the thickness direction is formed by controlling the discharge ratio of the casting head); in step S22, slurries a and b respectively enter the gradient blending casting head, and the gradient blending casting head continuously adjusts the supply ratio of slurries a and b in the casting direction (from the magnetically rich side to the conductively rich side along the thickness direction) according to a set program, so that in the interior of the freshly extruded wet film, the area near the magnetically rich side is mainly composed of slurry a. The film consists of multilayer composite foil powder a. The area near the conductive side is mainly composed of multilayer composite foil powder b in slurry b. The middle area is a smooth transition between the two powders in proportion. During this process, the sheet-like powders are bridged and combined by a polyvinyl butyral organic framework, maintaining a certain orientation and overlapping to form a wet film with a thickness of 1.0-1.3 mm. Subsequently, under the initial drying action, a large amount of ethanol-toluene mixed solvent evaporates, and polyvinyl butyral forms a continuous organic framework between the powders. Dibutyl phthalate ensures the flexibility of the organic framework, and the thickness of the initial green film shrinks to 0.7-0.9mm, but the gradient distribution of the internal multilayer composite foil powder a and multilayer composite foil powder b is not destroyed; in step S23, the preliminary green belt, while still having a small amount of residual solvent and a certain degree of adhesion on the surface, is screen-printed with silver-based paste in a predetermined area. The silver-based paste consists of 60-75wt% silver powder, 10-20wt% borosilicate glass powder, and 10-20wt% organic carrier. The silver powder has a particle size of 2-5μm, the borosilicate glass powder has a particle size of 1-3μm and a softening point of 750-850℃, and the organic carrier is usually a mixture of resin and organic solvent. In the subsequent sintering process, the silver powder in the silver-based paste undergoes solid-phase sintering to form a continuous conductive path. Borosilicate glass powder softens and wets the silver powder interface, forming a glass insulating boundary. This creates a localized frequency-selective structure in the silver-based region, enhancing the reflection capability of specific areas of high-frequency electromagnetic waves. Furthermore, during printing, the organic carrier facilitates the formation of a uniform coating of silver powder and borosilicate glass powder, achieving good wetting and integration with the polyvinyl butyral layer on the surface of the initial green belt, thus controlling the printing thickness to 10-30 μm. Subsequent drying allows the solvent in the organic carrier to evaporate, and the silver powder and borosilicate glass powder locally form a stable, solidified silver-based pattern, creating a silver-based green belt. Microscopically, the silver powder is not yet sintered but is already fixed in position, with the borosilicate glass powder dispersed within, awaiting softening and flow during subsequent sintering.
[0035] It is known that the viscosity of slurry a and slurry b formed after step S21 is controlled between 2000-4000 cP, ensuring that the slurry is neither too thin to maintain its shape nor too thick to flow through the gradient blending casting head. This guarantees the formation of a wet film with uniform thickness and continuous composition during the casting process. Furthermore, each multilayer composite foil powder a particle and multilayer composite foil powder b particle is externally coated with a stable organic coating composed of polyvinyl butyral and dispersant, while internally maintaining the Fe-Ni / Cu alternating multilayer structure obtained in step S1. This combination of external flowability and internal multi-interface structure provides conditions for leveraging the short diffusion distance advantage at lower sintering temperatures. The preliminary green strip obtained in step S22 exhibits a compositional gradient in the thickness direction and overall structural integrity, with the wet film extending from the magnetic-rich side to the conductive-rich side. The proportion of slurry a decreases while the proportion of slurry b increases, resulting in a continuous volume fraction change in the thickness direction of multilayer composite foil powder a and multilayer composite foil powder b. After initial drying, polyvinyl butyral is cured into a film, giving the initial green belt sufficient strength to prevent breakage during subsequent handling and printing. At the same time, the initial drying temperature ensures that the solvent is basically evaporated without causing the binder to shrink drastically, thus preventing the gradient structure from cracking due to uneven stress. The silver-based green belt formed in step S23 has local silver-enriched micro-regions. The high silver content in these micro-regions ensures the formation of a continuous conductive network during subsequent sintering. Borosilicate glass forms a glass phase encapsulation and interface layer. The organic carrier forms an initial organic framework after re-drying, which can be removed in subsequent steps, leaving a multiphase structure composed of silver powder and glass powder.
[0036] Understandably, step S21, by setting the binder ratio, ensures that slurry a and slurry b maintain good fluidity and dispersibility while retaining high solid content, achieving stable casting under high filling degree. This guarantees that the gradient sintered material has high density and good mechanical properties after sintering, thus providing good magnetic and electrical continuity for the electromagnetic shielding material. Simultaneously, polyvinyl butyral in the binder system is easily decomposed and removed during subsequent segmented degreasing, dibutyl phthalate acts as a plasticizer to prevent the green belt from becoming brittle during drying and handling, and the dispersant ensures that the powder does not agglomerate. This results in fewer defects, more stable magnetic loss and conductive paths in the final sintered medium, reducing fluctuations in shielding performance from the material's fundamental perspective. The initial green belt formed by the gradient casting in step S22 allows the magnetically rich precursor multilayer composite foil powder a and the conductive precursor multilayer composite foil powder b from step S1 to achieve continuous distribution in the thickness direction, transforming the original distribution in step S1, which was only present in the overall composition, into a continuous distribution. The magnetically rich and conductively rich ends of the upper section are spatially distributed and transformed into a real magnetic-conductivity gradient structure within the material. This allows the final electromagnetic shielding material to provide high permeability and magnetic loss in the magnetically rich region at low frequencies, and high conductivity and high reflectivity in the conductive region at high frequencies. The intermediate transition region softens impedance abrupt changes, achieving a smooth transition in the frequency response curve during broadband shielding. In step S23, silver-based paste is printed and dried again to introduce locally highly conductive micro-regions without damaging the initial green body gradient structure. This provides additional shielding reinforcement for the areas with the most severe high-frequency electromagnetic interference inside the power equipment. The silver powder forms a low-impedance surface conductive network during subsequent sintering, and the borosilicate glass powder, after softening, fixes the boundaries of the conductive micro-regions, thereby forming a local impedance adjustment layer. This allows these regions to selectively enhance the reflection and attenuation of high-frequency electromagnetic waves, thus superimposing local high-frequency optimization functions on the basis of overall gradient shielding, solving the problem that traditional uniform materials cannot simultaneously address local high-frequency interference hotspots.
[0037] It is important to emphasize that step S21, by enabling the powder to form a uniform slurry and maintaining the integrity of the multilayer structure, provides a foundation for the subsequent formation of materials with gradient structures, and ensures the stability of the component distribution and the absence of agglomeration during the casting process. This provides technical support for solving the problems of uneven composition and inconsistent performance in electromagnetic shielding materials. Step S22, through the casting process, achieves a continuous gradient transition of magnetic and conductive components in the material, enabling the electromagnetic shielding performance of the obtained electromagnetic shielding material to smoothly transition rather than abruptly in different frequency bands. This optimizes the broadband adaptability of the electromagnetic shielding material, allowing it to maintain a relatively balanced shielding effect over a wide frequency range, rather than experiencing excessive absorption or reflection in a certain frequency band. Step S23, through the printing and drying of the silver-based slurry, forms a local frequency-selective structure on the surface of the electromagnetic shielding material, providing a solution to the problem of local enhancement of mid-to-high frequency electromagnetic interference in power equipment. By enhancing the high-frequency reflection capability of the silver-rich micro-region in specific areas, it avoids the phenomenon of insufficient shielding in local areas, enabling the material to have more precise electromagnetic shielding function in different usage environments.
[0038] It is worth noting that step S21 uses a binder system consisting of 5-8 wt% polyvinyl butyral, 3-4 wt% dibutyl phthalate, 1-2 wt% dispersant, and the remainder being an ethanol-toluene mixed solvent. This system allows polyvinyl butyral to form a continuous organic framework under initial drying conditions at 40-60°C, which can then be readily decomposed in subsequent steps. Dibutyl phthalate acts as a plasticizer to ensure that the initial green belt and the silver-based green belt do not become brittle during handling and printing. The dispersant, combined with the ethanol-toluene mixture... The mixed solvent effectively wets the sheet-like multilayer composite foil powder a and multilayer composite foil powder b, allowing the high-solids slurry to maintain a moderate viscosity of 2000-4000 cP. Step S22 uses a casting speed of 0.6-0.8 m / min and a wet film thickness of 1.0-1.3 mm to ensure sufficient production capacity while allowing slurry a and slurry b enough time to complete shear mixing within the gradient blending casting head and form a stable proportional distribution at the outlet. The initial drying allows for the slow evaporation of the ethanol-toluene mixed solvent. To avoid excessively rapid drying that could cause surface hardening and internal solvent retention leading to blistering and cracking, a small amount of organic phase and solvent is retained to facilitate coupling between the subsequent silver-based slurry and the surface of the initial green strip. In step S23, the silver-based slurry consists of 60-75 wt% silver powder, 10-20 wt% borosilicate glass powder, and 10-20 wt% organic carrier. During subsequent sintering, the silver powder's lower sintering temperature forms a continuous conductive network, while the borosilicate glass powder forms the glass phase boundary. This fixes the position of the silver network and prevents it from over-wetting the matrix gradient sintering material. The 60-75 wt% silver powder ensures a continuous conductive path after sintering, while a content below 60 wt% will cause the conductive network to be interrupted, affecting high-frequency reflection capability. The subsequent drying allows the organic carrier to gradually volatilize, while the positions of the silver powder and glass powder remain fixed and do not crack due to rapid solvent evaporation. This ensures that the silver-based green strip maintains the integrity of the overall gradient structure and guarantees the geometric accuracy and adhesion of the silver-based region when entering step S3.
[0039] In one specific embodiment, in step S21, the binder comprises 6.5 wt% polyvinyl butyral, 3.5 wt% dibutyl phthalate, and 1.5 wt% dispersant, with the balance being an ethanol-toluene mixed solvent. The multilayer composite foil powder a and multilayer composite foil powder b have the same mass ratio to the binder, which is 72.5:27.5. The apparent viscosity of both slurry a and slurry b is 3000 cP. In step S22, the casting speed of the gradient blending casting head is 0.7 m / min, and the wet... The film thickness is 1.15 mm, the initial green belt thickness is 0.8 mm, and the initial drying temperature is 50 °C for 30 min. In step S23, the silver-based paste contains 67.5 wt% silver powder, 15 wt% borosilicate glass powder, and 17.5 wt% organic carrier. The silver powder has a particle size of 3.5 μm, the borosilicate glass powder has a particle size of 2 μm and a softening point of 800 °C, the printing thickness of the silver-based paste is 20 μm, and the re-drying temperature is 50 °C for 30 min.
[0040] Specifically, in step S3, after segmented degreasing of the silver-based green strip, it is subjected to low-temperature activation sintering, followed by high-temperature densification sintering to obtain a gradient sintered material. Step S3 specifically includes the following steps: Step S31: Place the silver-based green strip in a sintering furnace under a nitrogen protective atmosphere and perform low-temperature stage and medium-temperature stage in sequence to obtain green body a; In step S31, the heating rate in the low-temperature stage is 0.5-1℃ / min, the temperature is 200-250℃, and the duration is 1-2h; the heating rate in the medium-temperature stage is 0.5-1℃ / min, the temperature is 350-450℃, and the duration is 2-3h. Step S32: Raise the temperature of the environment where embryo a is located to the first temperature to obtain embryo b; In step S32, the first temperature is 780-820℃, the heating rate is 3-5℃ / min, and the duration is 1-2h; Step S33: Raise the temperature of the environment where the preform b is located to a second temperature and apply pressure to it to obtain a gradient sintering material.
[0041] In step S33, the second temperature is 860-900℃, the heating rate is 2-4℃ / min, the duration is 0.5-1h, and the pressure is 0.5-2MPa.
[0042] It should be noted that in step S31, the silver-based green belt first enters the sintering furnace under a nitrogen protective atmosphere and begins to undergo a low-temperature stage and a medium-temperature stage. In the low-temperature stage, the excess organic matter and solvent, namely the residues of polyvinyl butyral and dibutyl phthalate, can be removed by the low-temperature heating rate, preventing excessive decomposition of organic matter and material surface defects in the subsequent sintering process. The residual organic components in this stage begin to decompose, release gases and gradually disappear, and the gradient structure of the silver-based green belt and the silver-based local areas remain intact. At the same time, the slow heating and nitrogen protection in this stage effectively avoid the oxidation of the material and provide a clean environment for the subsequent sintering process. The subsequent medium-temperature stage further removes... Residual organic matter promotes micro-diffusion and initial solid solution between powder particles. The Fe-Ni and Cu multilayer structure begins to interact initially, resulting in preform a. The temperature at this stage is sufficient to promote the solid solution of Fe and Ni, but not enough to trigger high-temperature diffusion or grain growth, thus maintaining the integrity of the multilayer composite structure. This temperature can complete the complete decomposition of the binder while avoiding excessively high temperatures that could lead to premature large-scale diffusion of the Fe, Ni, and Cu system, thereby maintaining the integrity of the powder particle interface structure. In step S32, preform a enters the first sintering temperature stage, which enables the diffusion of Fe-Ni and Cu, allowing each element to undergo solid solution at a lower temperature and form a uniform alloy structure, resulting in preform b. The corresponding heating rate is... The process ensures uniform temperature distribution, preventing cracks or uneven expansion due to localized overheating. During this process, Fe, Ni, and Cu elements gradually diffuse into each other's crystal lattices within this temperature range, forming a relatively uniform solid solution in a short time. Since the temperature has not yet reached the melting point, this stage will not cause the preform a to melt or excessively diffuse, but it is sufficient to prepare for the subsequent high-temperature densification stage. In addition, the sintering volume shrinkage will bring about the initial densification of preform b, but the overall structure still maintains its original gradient distribution, and the grain size remains small. In step S33, preform b enters the second temperature stage of sintering. In this stage, by applying a pressure of 0.5-2 MPa, further densification of the interparticle contact interface is promoted. The close integration of the two stages enhances the density and mechanical strength of the preform b. During this process, the grains grow further, significantly increasing the density of the preform b. The solid solution of Fe-Ni and Cu gradually stabilizes, eliminating voids and pores to form a dense sintered structure, i.e., a gradient sintered material. Due to the application of appropriate pressure, stronger neck growth and bonding occur between the particles, further enhancing the structural stability of the gradient sintered material. In this stage, the preform b shrinks after sintering and forms a denser granular structure. The compositional gradient between the multilayer composite foil powder a and the multilayer composite foil powder b is effectively preserved. The sintering in the second temperature stage not only promotes the solid solution process but also provides structural support for the subsequent optimization of electromagnetic shielding performance.
[0043] It is known that in the low-temperature and medium-temperature stages of step S31, organic matter in the silver-based green roll is removed while its oxidation is prevented, ensuring the stability of the subsequent sintering process. Furthermore, the removal of organic matter allows the Fe-Ni and Cu components within the silver-based green roll to diffuse smoothly without causing uneven reactions or surface defects due to residual organic matter, thus providing favorable conditions for subsequent sintering. In the first temperature stage of step S32, the diffusion of Fe and Ni is enhanced, and the Fe-Ni and Cu system gradually forms a uniform alloy structure in the solid state. This stage promotes the solid solution of the green roll a at a lower temperature. The process avoids grain growth and interface defects that may occur at excessively high temperatures, allowing the obtained green body b to maintain its required gradient structure and laying the foundation for the densification process of high-temperature sintering. In the second temperature stage of step S33, the sintering temperature is further increased, and with appropriate pressure, the tight bonding and densification of particles are promoted. The high density and uniform solid solution formed at high temperature improve the mechanical strength and electromagnetic shielding performance of the obtained gradient sintered material, ensuring that no cracks or pores appear in the gradient sintered material during high-temperature sintering, maintaining the original composition gradient, and improving the overall density and strength.
[0044] Understandably, in step S31, the effective removal of organic matter ensures the smooth progress of the subsequent diffusion process and avoids the impact of gases generated by the decomposition of organic matter on the material. This allows Fe-Ni and Cu elements to diffuse smoothly and form uniform alloy particles, providing a stable foundation for the final electromagnetic shielding performance. In the first temperature stage of step S32, the solid solution diffusion of Fe and Ni enables the elements between the multilayer composite foil powder a and multilayer composite foil powder b to begin to homogenize, laying the foundation for subsequent high-temperature densification sintering. The diffusion reaction, combined with an appropriate heating rate and temperature, not only promotes the mutual solubility between elements but also effectively avoids excessive diffusion or grain growth, ensuring the structural stability of the material, achieving the homogenization of the internal structure of the material, and providing conditions for further densification. In the second temperature stage of step S33, by applying pressure and increasing the temperature, the bonding force between particles is enhanced, the density of the material is increased, ensuring the high density and high strength of the material, while maintaining the stability of the gradient structure. It also effectively eliminates voids in the material, improves mechanical properties, and ensures the conductivity of the electromagnetic shielding material in the high-frequency band.
[0045] It is worth noting that step S31 removes organic matter by slowly heating up and ensures that the element diffusion of the powder occurs at a lower temperature, preventing grain growth or excessive diffusion. This ensures that the diffusion rates of Fe, Ni, and Cu can be reasonably controlled during the subsequent sintering process, providing the necessary structural basis for high-frequency shielding performance. In step S32, the temperature of the first temperature stage promotes solid solution between Fe and Ni without excessively inducing grain growth or component separation, and the heating rate ensures the uniformity of the reaction, providing the necessary solid solution basis for subsequent densification sintering. In step S33, the temperature and heating rate of the second temperature stage, combined with the corresponding pressure, further bond the contact interfaces between particles, increasing the density of the gradient sintered material. This results in a better balance between absorption in the low-frequency band and reflection in the high-frequency band, ensuring the wide applicability of electromagnetic shielding performance.
[0046] In a specific embodiment, in step S31, the heating rate of the low-temperature stage is 0.75℃ / min, the temperature is 225℃, and the duration is 1.5h; the heating rate of the medium-temperature stage is 0.75℃ / min, the temperature is 400℃, and the duration is 2.5h; in step S32, the first temperature is 800℃, the heating rate is 4℃ / min, and the duration is 1.5h; in step S33, the second temperature is 880℃, the heating rate is 3℃ / min, the duration is 0.75h, and the pressure is 1.25MPa.
[0047] Specifically, in step S4, after surface smoothing treatment of the gradient sintering material, a nickel-phosphorus protective layer is formed on its surface by chemical plating to obtain the electromagnetic shielding material.
[0048] Step S4 specifically includes the following steps: Step S41: Perform surface planarization treatment on the gradient sintering material to make its surface roughness Ra 0.8-1.6μm; Step S42: A nickel-phosphorus protective layer is formed by electroless plating on the surface of the gradient sintering material to obtain an electromagnetic shielding material; wherein the thickness of the nickel-phosphorus protective layer is 1-2 μm, the phosphorus content is 6-10 wt%, and the plating temperature is 80-90℃.
[0049] It should be noted that in step S41, the surface of the gradient sintering material is leveled to improve its surface roughness, making the surface smoother and ensuring uniform adhesion of the subsequent coating. During this process, the surface roughness of the gradient sintering material is effectively reduced, smoothing out microscopic unevenness, microcracks, or micropores caused by the sintering process. This ensures the adhesion and stability of the subsequent electroless plating, avoiding problems such as peeling and blistering due to surface unevenness. In step S42, after the surface of the gradient sintering material is leveled, an electroless plating technique is used to form a 1-2 μm thick nickel-phosphorus protective layer on the surface. Specifically, this is achieved through electroless plating... The nickel-phosphorus process involves the uniform deposition of nickel and phosphorus onto the material surface through a chemical reaction, forming a nickel-phosphorus protective layer. This layer exhibits excellent corrosion resistance, wear resistance, and weldability. Furthermore, the formation of this protective layer improves the surface properties of electromagnetic shielding materials, making them more adaptable to the complex environments of power equipment. During this process, the nickel-phosphorus protective layer is uniformly deposited, forming a continuous coating with good adhesion. This effectively protects the surface of gradient sintered materials from external environmental erosion. In addition to increasing the surface hardness and durability of the material, the nickel-phosphorus protective layer further optimizes the electromagnetic properties of gradient sintered materials, particularly playing a crucial role in reflecting high-frequency electromagnetic waves.
[0050] It is known that after surface smoothing treatment, gradient sintering materials eliminate the micro-protrusions, rough surfaces, and cracked areas generated during the sintering process, providing a smooth and flat substrate for subsequent electroless plating. This ensures that the plating layer can adhere evenly and firmly to the surface, avoiding plating quality problems caused by surface unevenness during electroless plating, such as peeling, bubbles, or uneven thickness. The electroless nickel-phosphorus protective layer has excellent corrosion resistance and wear resistance. This coating not only provides physical protection but also improves the durability of electromagnetic shielding materials during use. Especially in the harsh environment of power equipment, the introduction of the nickel-phosphorus protective layer can effectively prevent the performance degradation of the electromagnetic shielding material surface caused by external friction, corrosion, or chemical reactions. At the same time, the nickel-phosphorus protective layer can also improve the electromagnetic response capability of the material in frequency selective surfaces (structures that selectively transmit or reflect electromagnetic waves at specific frequencies, through a composite structure formed by local high conductivity areas and insulating areas to enhance high-frequency reflection performance), improving the reflection capability of high-frequency electromagnetic waves and providing more effective electromagnetic shielding for power equipment.
[0051] It is worth noting that the surface smoothing treatment in step S41 adopts polishing or slight rolling process. This method can effectively remove the small protrusions, cracks and uneven parts of the surface that may be generated during sintering, providing a uniform surface base for subsequent electroless plating. The coating thickness of the nickel-phosphorus protective layer is 1-2μm. This thickness matches the surface structure of the electromagnetic shielding material, ensuring that the nickel-phosphorus protective layer can provide sufficient corrosion resistance and wear resistance without being too thick and affecting the electromagnetic properties of the material itself. In addition, the thickness of the nickel-phosphorus protective layer, the phosphorus content and the plating temperature of 80-90℃ are combined to ensure the uniformity and stability of the coating. This not only enhances the surface durability of the material, but also provides it with the ability to reflect high-frequency electromagnetic waves, solving the shortcomings of traditional electromagnetic shielding materials in high-frequency response capability.
[0052] In a specific embodiment, step S41 involves surface planarization of the gradient sintering material to achieve a surface roughness Ra of 1.2 μm; step S42 involves depositing a nickel-phosphorus protective layer onto the surface of the gradient sintering material using a chemical plating solution to obtain an electromagnetic shielding material; wherein the nickel-phosphorus protective layer has a thickness of 1.5 μm, a phosphorus content of 8 wt%, and a plating temperature of 85 °C.
[0053] The following is a comparison of various data between the electromagnetic shielding material obtained in Example 1 and traditional electromagnetic shielding materials, as shown in Tables 1, 2, and 3: Table 1 As shown in Table 1, Example 1 exhibits superior performance in low-frequency magnetic field shielding compared to traditional galvanized steel plates, aluminum plates, and copper plates. In particular, it demonstrates a significant advantage in magnetic permeability under low-frequency magnetic fields (10kHz and 100kHz). By optimizing the magnetic permeability gradient and low-frequency magnetic loss factor, the shielding effectiveness is improved, especially in the low-frequency band, where it can provide magnetic field absorption capacity that is 2-10 times higher than that of traditional materials.
[0054] Table 2 As shown in Table 2, in the mid-to-high frequency electromagnetic wave range, Example 1 exhibits superior reflection capability. Compared with traditional materials, especially in the 100MHz-1GHz frequency band, the shielding effectiveness is improved by 15-20dB, effectively reducing reflection abrupt changes and optimizing broadband shielding performance.
[0055] Table 3 As shown in Table 3, Example 1 is significantly superior to traditional materials in terms of bending strength, microhardness, and corrosion resistance. In particular, in terms of bending strength and corrosion resistance life, it exhibits stronger mechanical properties and environmental adaptability compared to aluminum and copper plates, further improving the stability and long-term usability of the shielding material in harsh working environments.
[0056] Example 2: This embodiment provides an electromagnetic shielding material for power equipment, which is prepared according to the preparation method described in Example 1.
[0057] Example 3: This embodiment describes the application of an electromagnetic shielding material for power equipment prepared according to the method described in Example 1 in the field of electromagnetic interference suppression.
[0058] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an electromagnetic shielding material for power equipment, characterized in that, The preparation method includes the following steps: Step S1: Prepare multilayer composite foils a and b, which are composed of alternating Fe-Ni layers and Cu layers, and break them into multilayer composite foil powders a and b, respectively; wherein the outermost layer of multilayer composite foil powder a is Fe-Ni layer, and the outermost layer of multilayer composite foil b is Cu layer. Step S2: Mix the adhesive with multilayer composite foil powder a and multilayer composite foil powder b respectively to obtain slurry a and slurry b. Then, perform gradient casting on slurry a and slurry b to obtain a preliminary green strip. Then, print the silver-based slurry on the preliminary green strip to obtain a silver-based green strip. Step S3: After segmented degreasing of the silver-based green strip, it is subjected to low-temperature activation sintering, followed by high-temperature densification sintering to obtain a gradient sintered material. Step S4: After surface smoothing treatment of the gradient sintering material, a nickel-phosphorus protective layer is formed on its surface by chemical plating to obtain the electromagnetic shielding material.
2. The method for preparing electromagnetic shielding material for power equipment according to claim 1, characterized in that, Step S1 specifically includes the following steps: Step S11: First, in the roll-to-roll electrodeposition equipment, the electrodeposition cathode carrier a is sequentially passed through the magnetic layer electrodeposition tank, the cleaning tank, and the conductive layer electrodeposition tank. After multiple cycles, Fe-Ni and Cu layers are alternately deposited on the electrodeposition cathode carrier a to obtain a multilayer composite foil a with Fe-Ni layer as the outermost layer. Subsequently, the electrodeposition cathode carrier b is sequentially passed through the conductive layer electrodeposition tank, the cleaning tank, and the magnetic layer electrodeposition tank. After multiple cycles, Cu and Fe-Ni layers are alternately deposited on the electrodeposition cathode carrier b to obtain a multilayer composite foil b with Cu layer as the outermost layer. Step S12: By shearing pre-shredding and inert atmosphere airflow pulverization, multilayer composite foil a and multilayer composite foil b are respectively made into sheet powder, resulting in multilayer composite foil powder a and multilayer composite foil powder b.
3. The method for preparing electromagnetic shielding material for power equipment according to claim 2, characterized in that, In step S11, the magnetic layer electrodeposition tank is filled with electrolyte a, which contains 80-120 g / L ferrous sulfate and 5-15 g / L nickel sulfate, and the pH value of electrolyte a is 2.5-3.5, the temperature is 45-55℃, and the current density of the magnetic layer electrodeposition tank is 8-12 A / dm³. 2 The conductive layer electrodeposition tank is filled with electrolyte b, which contains 60-100 g / L copper sulfate and 80-120 g / L sulfuric acid, and the temperature of electrolyte b is 25-35°C. The current density of the conductive layer electrodeposition tank is 4-6 A / dm³. 2 The total number of layers of the multilayer composite foil a and the multilayer composite foil b are both 40-80 layers, the thickness of a single layer is both 80-200nm, and the total thickness is both 6.4-16μm. The atomic ratio of (Fe-Ni) to Cu in the multilayer composite foil a is (55-65):(35-45), and the atomic ratio of (Fe-Ni) to Cu in the multilayer composite foil b is (30-40):(60-70). In step S12, the average particle size D50 of the multilayer composite foil powder a and the multilayer composite foil powder b are both 15-35μm, the particle size is both 5-45μm, the powder thickness is both 2-4μm, and the aspect ratio is both >10.
4. The method for preparing electromagnetic shielding material for power equipment according to claim 1, characterized in that, Step S2 specifically includes the following steps: Step S21: Mix multilayer composite foil powder a with adhesive in a certain proportion and then ball mill to obtain slurry a; mix multilayer composite foil powder b with adhesive in a certain proportion and then ball mill to obtain slurry b; Step S22: After feeding slurry a and slurry b into the gradient blending casting head, adjust the feeding ratio of slurry a and slurry b, and output the wet film from the gradient blending casting head along the magnetic side to the conductive side to form a wet film. Then, perform initial drying on the wet film to obtain a preliminary green belt. Step S23: Silver-based paste is printed onto a predetermined area on the initial green belt using screen printing, and then dried again to obtain a silver-based green belt.
5. The method for preparing electromagnetic shielding material for power equipment according to claim 4, characterized in that, In step S21, the adhesive comprises 5-8 wt% polyvinyl butyral, 3-4 wt% dibutyl phthalate, 1-2 wt% dispersant, and the balance being an ethanol-toluene mixed solvent. The multilayer composite foil powder a and multilayer composite foil powder b have the same mass ratio to the adhesive, which is (70-75):(25-30). The apparent viscosity of slurry a and slurry b is 2000-4000 cP. In step S22, the casting speed of the gradient blending casting head is 0.6-0.8 m / min, the thickness of the wet film is 1.0-1.3 mm, the thickness of the initial green belt is 0.7-0.9 mm, and in the wet film, along the direction from the magnetic side to the conductive side, the proportion of slurry a decreases sequentially, while the proportion of slurry b increases sequentially. The initial drying temperature is 40-60℃ and the time is 20-40 min. In step S23, the silver-based paste contains 60-75 wt% silver powder, 10-20 wt% borosilicate glass powder, and 10-20 wt% organic carrier. The silver powder has a particle size of 2-5 μm, the borosilicate glass powder has a particle size of 1-3 μm and a softening point of 750-850℃, the printing thickness of the silver-based paste is 10-30 μm, and the re-drying temperature is 40-60℃ and the time is 20-40 min.
6. The method for preparing electromagnetic shielding material for power equipment according to claim 1, characterized in that, Step S3 specifically includes the following steps: Step S31: Place the silver-based green strip in a sintering furnace under a nitrogen protective atmosphere and perform low-temperature stage and medium-temperature stage in sequence to obtain green body a; Step S32: Raise the temperature of the environment where embryo a is located to the first temperature to obtain embryo b; Step S33: Raise the temperature of the environment where the preform b is located to a second temperature and apply pressure to it to obtain a gradient sintering material.
7. The method for preparing electromagnetic shielding material for power equipment according to claim 6, characterized in that, In step S31, the heating rate of the low-temperature stage is 0.5-1℃ / min, the temperature is 200-250℃, and the duration is 1-2h; the heating rate of the medium-temperature stage is 0.5-1℃ / min, the temperature is 350-450℃, and the duration is 2-3h. In step S32, the first temperature is 780-820℃, the heating rate is 3-5℃ / min, and the duration is 1-2h; In step S33, the second temperature is 860-900℃, the heating rate is 2-4℃ / min, the duration is 0.5-1h, and the pressure is 0.5-2MPa.
8. The method for preparing electromagnetic shielding material for power equipment according to claim 1, characterized in that, Step S4 specifically includes the following steps: Step S41: Perform surface planarization treatment on the gradient sintering material to make its surface roughness Ra 0.8-1.6μm; Step S42: A nickel-phosphorus protective layer is formed by electroless plating on the surface of the gradient sintering material to obtain an electromagnetic shielding material; wherein the thickness of the nickel-phosphorus protective layer is 1-2 μm, the phosphorus content is 6-10 wt%, and the plating temperature is 80-90℃.
9. An electromagnetic shielding material for power equipment, characterized in that, The electromagnetic shielding material for power equipment is obtained by the preparation method according to any one of claims 1-8.
10. The application of an electromagnetic shielding material for power equipment prepared by any one of claims 1-8 in the field of electromagnetic interference suppression.
Citation Information
Patent Citations
Preparation method of electromagnetic shielding multi-layer composite material in electric vacuum device
CN102126112A
Preparation method of broadband multilayer electromagnetic shielding film
CN118139399A